(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Taekwondo is a traditional Korean martial art combining foot (tae) and hand (kwon) techniques. It is among the most popular martial arts worldwide and became an official Olympic discipline in 2012. Taekwondo can be divided into two types kyorugi and poomsae, kyorugi is full-contact sport, such as The Olympic Taekwondo, and the other is non-contact sport, which mainly focuses on performances and demonstrations, the non-contact sport known as “Poomsae”. In order to achieve results in various competitions, the training of ordinary athletes focuses on sparring (Olympic style) taekwondo. In recent years, however, many experienced athletes have begun to engage in mind training centered on the unity of posture (Poosae). Poosae is the only non-contact training in taekwondo. Poomsae consists of 13 defined patterns of movement, which are repeated over and over in practice.